Taxonomic status of the African buffalo - (:unkn) unknown (My University, 2023)
The development of genetic studies on the African buffalo helped: to delineate subspecies number based on restricted gene flow criteria to either two or maximally three; to define three Conservation Units requiring separate management efforts, namely: (1) Eastern–Southern Africa, (2) the West–Central African forests and (3) the West–Central African savannas; to uncover major evolutionary demographic events, with the earliest identified expansion occurring 500–1000 kya; to evidence a strong population decline in Eastern–Southern Africa starting around 5 kya, and proposed to result from both climatic factors and explosive growth of human populations and their cattle. However, buffalo populations still display high genetic diversity and low genetic differentiation, and show primary sex-ratio distortion and high-frequency deleterious alleles in the buffalo genome and their potential effect on population demography and viability. Future management efforts are necessary to maintain gene flow, with the challenge that populations become more fragmented, distributed into a mosaic of conserved areas.
Keywords: African Research